Farrow-to-Weaned Pig Cost-Return Budget - Dhuyvetter, Kevin C.; Tokach, Mike D.; Dritz, Steve S.; DeRouchey, Joel; Tonsor, Glynn T. (My University, 2012)
This publication provides estimated cost and returns for a farrow-weaned pig operation.
MF2153_2012_01
Keywords: MF2153; Livestock; Economics; MF